New monomer for hydrophobic acrylic copolymers and their novel properties - De Vries, Andrew Robert (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DSc (Chemistry and Polymer Science))--University of Stellenbsoch, 2006.